9th International Symposium on High-Temperature Metallurgical Processing (The Minerals, Metals & Materials Series,, 2018)
In recent years, global metallurgical industries have experienced fast and prosperous growth. High-temperature metallurgical technology is the backbone to support the technical, environmental, and economical needs for the growth. This collection features contributions covering the advancements and developments of new high-temperature metallurgical technologies and their applications to the areas of processing of minerals; extraction of metals; preparation of metallic, refractory and ceramic materials; treatment and recycling of slag and wastes; and saving of energy and protection of environment.The volume will have a broad impact on the academics and professionals serving the metallurgical industries around the world.